Pomegranate Juice Inhibits Periodontal Pathogens Biofilm in vitro - Armelia Sari Widyarman; Olivia Puspita Suhalim; Dhara Nandary; Citra Fragrantia Theodorea (Scientific Dental Journal, 2018)
Background: Pomegranate (Punica granatum) fruits are commonly regarded as medicinal plant in Indonesia, and the polyphenols found in pomegranate juice (punicalagin and ellagic acid) have been shown to have antibacterial properties. Objectives: Using monospecies and multispecies biofilms, we sought to examine the effects of pomegranate juice on the viability of three periodontal pathogens: Porphyromonas gingivalis, Aggregatibacter actinomycetemcomitans, and Treponema denticola. Methods: Biofilm assays were performed using crystal violet. Pomegranate juice was obtained from pomegranates using a juicer, and the juice was then diluted into different concentrations with phosphate saline buffer. The three pathogens were cultured in both monospecies and multispecies plates. Pomegranate juice was then added to each biofilm well. These were then incubated for 1h, 6h, or 24h, after which the optical density (OD) of the biofilm mass was measured using a microplate-reader (490 nm). Biofilm without treatment was used as a negative control and 0.2% chlorhexidine gluconate as a positive control. Data were analyzed with a one-way ANOVA; the level of significance was set at p<0.05. Results: Compared to the negative control, biofilm mass was significantly decreased after treatment with pomegranate juice across all concentrations and incubation times, for both monospecies and multispecies biofilm (p<0.05). The best results were achieved with P. gingivalis biofilm, with 100% concentration (OD 0.34 ± 0.03); A. actinomycetemcomitans, 50% concentration (OD 0.22 ± 0.01); and T. denticola, with 25% concentration (OD 0.87 ± 0.08), as well as with a multispecies biofilm with a 50% concentration in 1h incubation time (OD 0.09 ± 0.02). Conclusion: Pomegranate juice effectively inhibited the biofilm formation of P. gingivalis, A. actinomycetemcomitans, and T. denticola. Pomegranate juice may therefore be used as an alternative therapy in preventing periodontal disease. Additional research should explore this effect in an environment that mimics oral cavities.